Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5797/jnet.oa.2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stenting for Intracranial Internal Carotid Artery Stenosis Using Flow Reversal

Abstract: Objective: The safety of stenting for intracranial internal carotid artery stenosis using flow reversal embolic protection was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“… 7) Matsumoto et al reported a case of direct CCF during withdrawal of a stent retriever device for the treatment of acute middle cerebral artery occlusion. 8) …”
Section: Classification and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“… 7) Matsumoto et al reported a case of direct CCF during withdrawal of a stent retriever device for the treatment of acute middle cerebral artery occlusion. 8) …”
Section: Classification and Etiologymentioning
confidence: 99%
“…7) Matsumoto et al reported a case of direct CCF during withdrawal of a stent retriever device for the treatment of acute middle cerebral artery occlusion. 8) Regarding the location of fistulas, the most frequent location of direct CCF was reported to be the proximal horizontal intracavernous segment of the ICA, followed by the junction of the horizontal and ascending segments. 9)…”
Section: Introductionmentioning
confidence: 99%